Economic evaluations of prophylaxis with clotting factor for people with severe haemophilia: why do the results vary so much?. (19th September 2012) - Miners, A. H.
Summary A number of studies examining the cost effectiveness of haemophilia prophylaxis have been published, but they report a wide range of results. The aim of this study was to explain why the results from existing economic evaluations of prophylaxis with clotting factor vary so much and to suggest areas of further research that will help to generate stronger economic evidence. Results from a previous systematic review were updated using a textword search of a number of electronic databases. Eleven economic evaluations were identified. They reported incremental cost‐effectiveness ratios for prophylaxis ranging from 'cost saving and clinically beneficial' (i.e. 'dominant') to over €1 million per additional quality‐adjusted life year (QALY) if prophylaxis replaces treatment following a bleed. A number of reasons are likely to explain this breadth of results, most notably differences in choice of time horizon, estimates of treatment effect, clotting factor unit cost, discount rates and definitions of prophylaxis. Although the existing cost‐effectiveness literature for haemophilia prophylaxis appears to report a wide range of results, closer inspection suggests that differences are largely explained by a number of design features. Some are likely to reflect local economic conditions and should be expected. However, others, such as differences in the choice of appropriate time horizon, are more concerning as they reflect differences in opinion over appropriate methodology. A number of studies to help address these evidence gaps are suggested: however, it is also recommended that analysts continue to adhere to established conventions when conducting and reporting economic evaluations.